THE EFFECT OF ICT-BASED INTERACTIVE GAME ON ACHIEVEMENT MOTIVATION AND ENGLISH ACHIEVEMENT OF 6th GRADE STUDENTS IN PUBLIC ELEMENTARY SCHOOL IN CLUSTER 4 OF SUKASADA DISTRICT, BULELENG REGENCY IN ACADEMIC YEAR 2016/2017 - ., Ni Putu Ratna Puspitadewi; ., Dra.Ni Made Ratminingsih, MA; ., Made Hery Santosa, S.Pd, M.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini bertujuan untuk mengetahui pengaruh dari permainan interatif berbasis ICT terhadap motivasi prestasi, prestasi Bahasa Inggris, dan secara simultan terhadap motivasi prestasi dan prestasi Bahasa Inggris siswa. Penelitian experimental ini mengambil 174 siswa sekolah dasar sebagai populasi di gugus 4 kecamatan Sukasada, Kabupaten Buleleng Tahun Akademik 2016/2017, dimana 44 siswa yang melibatkan 22 siswa dari SD Negeri 3 Sukasada menjadi kelompok kontrol dan 22 siswa dari SD Negeri 4 Sukasada sebagai kelompok eksperimen. Mereka dipilih sebagai sampel penelitian melalui teknik random sampling. Data telah dikumpulkan melalui kuisioner motivasi prestasi dan post-test. Data tersebut dianalisis menggunakan ANAVA dan MANOVA satu jalur dengan SPSS 22.0. hasil penelitian menunjukkan bahwa, pertama, siswa yang diajarkan permainan interaktif berbasis ICT memiliki motivasi prestasi yang lebih baik daripada siswa yang diajarkan dengan teknik konvensional, kedua, siswa yang diajarkan permainan interaktif berbasis ICT memiliki prestasi Bahasa Inggris yang lebih baik daripada siswa yang diajarkan dengan teknik konvensional, ketiga terdapat pengaruh simultan dari permainan interaktif berbasis ICT terhadap motivasi prestasi dan prestasi Bahasa Inggris siswa.Kata Kunci : Motivasi Prestasi, Permainan Interaktif Berbasis ICT, Prestasi Bahasa Inggris, pelajar pemula This research purposed to investigate whether or not there was a significant effect on the use of ICT based interactive game on students’ achievement motivation and English achievement of the 6th grade of primary school. This quasi-experimental research implemented post-test only control group design. The population of this research was all the 6th grade of primary school in cluster 4 in Sukasada district. This research administered cluster random sampling to determine the sample of this research. As the result of administering cluster random sampling, the sample of this study was 22 students of 6th grade students in SD Negeri 3 Sukasada as the experimental group and 22 students of 6th grade in SD Negeri 4 Sukasada as the control group. The data were gathered by achievement motivation questionnaire and a post-test for both group. Then the data were analyzed by using one-way ANOVA and MANOVA assisted by SPSS 22.0. The findings show that, first, the students who were taught by ICT-based interactive game achieved better achievement motivation than those who were taught by conventional teaching, second, the students who were taught by ICT-based interactive game achieved better English achievement than those who were taught by conventional teaching, and third, the was a simultaneous effect of ICT-based interactive game on students’ achievement motivation and English achievement.keyword : ICT-based interactive game, achievement motivation, English achievement, young learners